Analysis of the property company's stock price forecasting with ARIMA Methods (case study in Ciputra Property CTRP.JK) - Fildananto, Asdi Atmin; Sulistiowati, Sulistiowati; Susilo, Tegar Heru (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Investments in shares offering high profits, but also risky. Ciputra Property Company is one of The property company that has been listed in the Stock Exchange (Indonesia Stock Exchange) with code CTRP.JK. Value stock price is always changing according to the world economic conditions. To complement with the rapid changes in order to avoid losses, this research propose a method capable to forecast stock price shares in the future. One of the forecasting method appropriate for forecasting is ARIMA. ARIMA has several models and the best model is the model which produces the smallest error rate. this research shows that ARIMA (0,1,1) is the best forecasting model with the smallest error rate of 2.64% to forecast Ciputra Property's stock price.